Effect of Remaxol on the efficiency of standard treatment for infiltrative pulmonary tuberculosis - Volchegorsky, I A; Novoselov, P N; Ushkareva, E V (Terapevtic̆eskii arhiv, 2016)
To investigate the effect of Remaxol on the efficiency of standard treatment in patients with infiltrative pulmonary tuberculosis (IPT). The results of treatment were analyzed in 90 patients with new-onset IPT in the phase of decay who received basic tuberculosis treatment regimens I, IIb, and IV. In addition, a study group of 45 patients used dropwise intravenous Remaxol 400 ml daily and a control group 45 patients had dropwise intravenous 5% glucose solution 400 ml daily. All the patients underwent clinical, laboratory and instrumental (X-ray) examinations over time. The incorporation of remaxol into the combination treatment of IPT enhanced the efficiency of therapy, which manifested as reductions in the hepatotoxicity of etiotropic drugs and in the degree of dysproteinemia and as accelerated destructive regression in tuberculous infiltrates with a subsequent decrease in the need for phthisiosurgical care. Remaxol included into the standard complex treatment regimens for IPT contributed to the rapider normalization of laboratory parameters of the liver and to the accelerated regression of destructive changes in the tuberculous infiltrates. Incorporation of remaxol into the combination treatment of patients with IPT enhances the efficiency of its therapy, promotes the rapider normalization of laboratory indices of the liver and the accelerated regression of destructive changes in tuberculous infiltrates, which reduces the need for phthisiosurgical care.